INCOMPATIBLE BUSINESS BEHAVIOR TOWARD ISLAMIC ETHICS: A STUDY ON THE PRACTICES OF RIBA AND BANK INTEREST - Hardiati, Neni; Anwar, Syahrul (CURRENT ADVANCED RESEARCH ON SHARIA FINANCE AND ECONOMIC WORLDWIDE, 2021)
Various kinds of interpretations of usury and interest in modern financial institutions (banks), both from jurists and Muslim economists, seem to occur because the 'illat usury put forward by the jurists is seen as inaccurate in the development of Islamic legal thought. Gharar which is translated as speculation is equated with gambling because of the uncertainty for the parties (seller and buyer). This research uses a literature study, which is carried out by collecting, studying and reviewing books, scientific magazines and related documents such as theses and scientific journals. Many modern societies carry out such practices, such as buying and selling agricultural products that are still on the land with a wholesale system. When viewed from the ethical side of Islamic transactions, both usury, interest and gharar violate the ethics of transactions. Ethical considerations prohibiting usury, interest and gharar, due to unfairness, exploitation and unproductiveness. While the system of economic ethics emphasizes products, fairness and honesty in trade, and fair competition. In this case, good ethics will give good business, good ethics: good business. Ethics that is in the spotlight in this study, especially ethics in the operations and transactions of Islamic financial institutions. Then the sharia financial institutions in question include sharia banking, sharia pawnshops, sharia insurance, and sharia capital markets, all of which are some forms of representation of sharia macro financial institutions that are certain. have a significant impact on the nation's economic development. So that behavior that is not in accordance with Islamic ethics, such as related to usury and bank interest, must be avoided for Muslims.